Feasibility study on mesophillic fermentation of tropical fruit waste into cleaning agents - Ng, Robin Pei Yi (2017)
Acetic acid, colloquially known as a “miracle cleaner”, is a common ingredient found in disinfectants and cleaners for its ability to kill fungus and microbes. It can be extracted from fruits and vegetable waste through bioconversion processes. This paper aims to evaluate the viability of anaerobic fermentation of tropical fruit waste to produce a cleaning agent that possesses acetic acid, using only items found in the typical household. A survey was conducted to determine the ergonomic considerations for the fermentation process. A recycling setup was designed and implemented based on the considerations to ferment the pineapple and durian fruit peels.